2024
DOI: 10.1021/acsinfecdis.3c00649
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Malaria: Shedding Light on Pathogenic Depths

Sangita Dey,
Salini Mohapatra,
Manoj Khokhar
et al.

Abstract: Malaria, a life-threatening infectious disease caused by Plasmodium falciparum, remains a significant global health challenge, particularly in tropical and subtropical regions. The epidemiological data for 2021 revealed a staggering toll, with 247 million reported cases and 619,000 fatalities attributed to the disease. This formidable global health challenge continues to perplex researchers seeking a comprehensive understanding of its pathogenesis. Recent investigations have unveiled the pivotal role of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 154 publications
(456 reference statements)
0
2
0
Order By: Relevance
“…PfEMP1 proteins incorporated into ECs and immune cells can promote inflammation [6,105] TIM-1 and TIM-4 (on immune cells and possibly on brain microglia) Immune-cell activation [6,7,95] BAI-1 (on neurons and cerebral ECs) [6] Relevant to the confusion surrounding the role of the CD36 cell receptor in CM, our review identified studies (and expert reviews) indicating that although cerebral ECs may express little CD36, iRBC-platelet-EC "bridge binding" within cerebral microvessels means the CD36 expressed by platelets can cause CD36-dependent microvascular obstruction in CM [9]. A study of children with malaria showed all Pf-parasite isolates but 1 (70 of 71) bound to CD36 [51].…”
Section: Tsp (On Ecs and Possibly On Brain Microglia)mentioning
confidence: 99%
See 1 more Smart Citation
“…PfEMP1 proteins incorporated into ECs and immune cells can promote inflammation [6,105] TIM-1 and TIM-4 (on immune cells and possibly on brain microglia) Immune-cell activation [6,7,95] BAI-1 (on neurons and cerebral ECs) [6] Relevant to the confusion surrounding the role of the CD36 cell receptor in CM, our review identified studies (and expert reviews) indicating that although cerebral ECs may express little CD36, iRBC-platelet-EC "bridge binding" within cerebral microvessels means the CD36 expressed by platelets can cause CD36-dependent microvascular obstruction in CM [9]. A study of children with malaria showed all Pf-parasite isolates but 1 (70 of 71) bound to CD36 [51].…”
Section: Tsp (On Ecs and Possibly On Brain Microglia)mentioning
confidence: 99%
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. 2 phosphatidylserine (PS) which is a key ligand in Pf infection [7]. Adhesive PfEMP1-expressing iRBCs can cause mechanical microvessel obstruction that can substantially reduce blood flow, damage tissues (like vascular endothelium), and trigger inflammation.…”
Section: Introductionmentioning
confidence: 99%